Comparative Experimental Study of Drying Temperatures (30°C vs 50°C) on Tannin and Mineral Retention in Moringa oleifera Leaves - Fitriyani, Aris; Kuhu, Maisje Marlyn; Widjijati, Widjijati (Journal of Applied Nursing and Health, 2026)
Background: Moringa oleifera leaves are nutrient-rich plant materials containing minerals and bioactive compounds with potential food and health applications. Drying temperature may affect their composition through moisture reduction and concentration effects. However, evidence comparing moderate drying temperatures (30°C and 50°C) and their impact on tannin and mineral content remains limited. This study aimed to evaluate the effects of drying at 30°C and 50°C on tannin and selected mineral concentrations in moringa leaves. Methods: A quantitative comparative laboratory experimental study was conducted using non-human plant samples. Fresh moringa leaves were dried at 30°C and 50°C under controlled conditions, with each treatment performed in triplicate. Tannin content was determined using UV–Visible spectrophotometry with calibration-based quantification, while mineral concentrations of calcium (Ca), magnesium (Mg), potassium (K), sodium (Na), and iron (Fe) were measured using Atomic Absorption Spectrophotometry (AAS) or ICP-OES. Inferential statistical analyses were conducted following assumption checks to compare measured concentrations between treatments. Results: Drying at 50°C produced consistently higher measured concentrations of tannins and minerals compared with drying at 30°C, indicating a coherent temperature-associated pattern across all analyzed parameters. Iron exhibited the largest numerical difference between treatments. These findings suggest that drying temperature influenced the measured chemical composition of moringa leaf powder, most likely through enhanced moisture reduction and concentration-related analytical effects. Conclusion: Moderate drying temperature (50°C) increased measured tannin and mineral concentrations relative to 30°C under laboratory conditions. However, these differences should be interpreted cautiously, as they likely reflect concentration effects rather than true nutrient retention or improved nutritional efficacy. Further studies incorporating moisture-normalized analysis, bioavailability assessment, and functional evaluation are required before translating these findings into clinical or public health recommendations